Educação em direitos humanos em práticas da pedagogia institucional: aprendizagem da democracia em conselho de classe - Araújo, Kleber de (2015)
In this research, we studied the learning of democracy in the context of Class Council, according to the guidelines of the Institutional Pedagogy (IP), in order to demonstrate the feasibility of a Human Rights Education (HRE) for pedagogical practices that model. The hypothesis created was that democracy learning is possible in the Class Council, provided they take into account the practices and training of HRE, as well as the fundamental principles and IP devices. To evaluate this hypothesis, it has been considered that Human Rights (HR) and democracy go together and showed up as contribution to Human Rights Education (HRE), from its definition, its foundations, its historical and its challenges (BITTAR, 2007, 2009; BENEVIDES, 2007; CARBONARI, 2007; COMPARATO, 2010; DALLARI, 2007; VIOLA, 2007). As a pedagogical proposal for the learning of a democratic culture in school, defended by (ARAÚJO, 2002; BOBBIO, 2000, 2004, 2006; BRANDÃO, 2013; CELLIER, 2000; PERRENOUD, 2005; ROSENFIELD, 1999; SAVIANI, 2009; TOSSI, 2013)). On the other hand, point out the contribution of the Institutional Pedagogy (IP) through the principles and devices, the main theoretical (ANDRADE, 2009; CAMINHA, 2012; HÉVELINE; ROBBES, 2009; IMBERT, 1994; OURY; SANCHES, 2002; VASQUEZ, 1967; 1977; PAIN, 2009, 2010, 2012;) competing for a HRE as a viable democratic practice this articulation. The methodology consisted of a case study to investigate the learning of democracy that had school practices involving the class council according to IP: the first, recorded in documentary of a private school in France; the second, recorded on video in a public school in Paraiba, Brazil. Addition, the result was: democracy learning is possible, as well as its construction in school spaces (among them, the Class Council according to PI), intrinsically associated value human rights, with the participation of people in decision-making possible to be shared.